Formação continuada e desenvolvimento profissional de professores da educação básica que participam de um programa de inserção profissional - Teles, Nayana Cristina Gomes (2019)
The objective of this research was to analyze the Educational Tutorial Program offered to the beginning teachers by the Municipal Secretary of Education of Manaus-AM about possible contributions to the Professional Development of the teachers of the network. This program assists teachers in the probationary stage in the municipal network, regardless of whether or not they have experience in teaching. The rationale for studying it stems from the interest in learning about good continuing education practices and understanding the factors that are associated with their success within the context in which they were conceived. In addition, initiatives to support the insertion of the beginning teacher are still rare in Brazil. The research utilized the qualitative approach that allows to apprehend the interactions in which the senses are produced and the meanings constructed. The methodological procedures chosen for the data collection were the semistructured interview and the observation, complemented with the documentary analysis. Semi-structured interviews were carried out with managers, coordinators, teacher trainers (tutors) and tutored teachers (beginners in the network), besides the observation of three tutoring sessions. The review of the literature that underpinned this research included theorists such as Carlos Marcelo (1999, 2009, 2010), Cunha (2005,2010), Day (2001), Imbernón (2006, 2010), Lima (2004, 2006), Vaillant and Marcelo (2012), among others. The data revealed a predominantly positive evaluation of the program by managers, coordinators, tutors and tutors. The main gains made by managers were: construction proposa of continuing education for beginning teachers; the institutionalization of the training of trainers; the construction of competence matrices; and the opportunity to discuss the probationary stage and the evaluation processes of the network teachers. With regard to the negative points and challenges that the program faces, two were highlighted in the speech of managers and tutors: the mobility of teachers in the network and the logistics involved in the displacement of trainers between schools. The positive aspects mentioned by the tutors were: a customized training; turn more directly to student learning; make a perceptible impact on student learning and behavior; being forming at the same time as forming the beginner. Beginning teachers, on the other hand, reported positive aspects of the program: the support and guidance offered by the tutor; the possibility of reflecting on their practices and the change in their way of working. The negative points mentioned by the tutors were: the time available for the formations; absence of space for the sessions; tutoring is a program aimed only at teachers on probationary stage; and the absence of a follow-up of the teachers who graduated from the program. We conclude that the Educational Tutorship Program has been successful in favoring the insertion of the new teachers of the network. However, we believe that it is necessary to move towards a more collaborative and integrated perspective of the school routine, since the program has failed to integrate into the school context as a whole and to promote peer collaboration. The expansion of tutoring for school management may be a prospect of progress in this direction